Stunting in Indonesia: Why is it Increasing? - Handayani Madania Insani (Journal of Applied Food and Nutrition, 2020)
The incidence of stunting in Indonesia has increased by 2.1% according to data presented by Basic Health Research in 2018 with a total percentage of 27.5% in 2016 and increased to 29.6% in 2017. This study is a descriptive study with a systematic review method. . Seeing the causes and prevalence of stunting as well as government and community efforts in tackling stunting is the goal of this study. The results showed that stunting cases in 2018 increased by 2.1% to 29.6%. Stunting in Indonesia is mostly caused by difficulty in accessing nutritious food, lack of exclusive breastfeeding, low birth weight (LBW) and low education level and parental income. The government has made various efforts such as intervention in various sectors, however, the incidence of stunting is still quite high. Thus, to tackle the incidence of stunting, collaboration with the community is needed to be more concerned and aware of knowledge related to balanced nutrition, especially for pregnant women, maternity mothers, toddlers and children.